2020
DOI: 10.9734/jaeri/2020/v21i830159
|View full text |Cite
|
Sign up to set email alerts
|

Insecticidal Activity of Ageratum conyzoides (Asteraceae) Aqueous Extracts against the Grasshopper Zonocerus variegatus (Orthoptera: Pyrgomorphidae)

Abstract: Ageratum conyzoides (Asteraceae) is an annual plant with insecticidal activity against some insect pests. The present study was designed to evaluate the insecticidal activity of aqueous extracts (infusion and maceration) of A. conyzoides against the pest grasshopper Zonocerus variegatus (Orthoptera, Pyrgomorphidae). Concentrations of 0, 10, 30, 100 & 300 µg/ml were prepared and administrated through injection to grasshoppers. Mortality rate was recorded for adult grasshoppers each day until the 9th day of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…and Diaphania hyalinata. Furthermore, exposure of Zonocerus variegatus to 10 mg ml -1 to 300 mg ml -1 of A. conyzoides for 4 days to 5 days induced 100% mortality of the insect pest (Ingrid et al, 2020). Similar trials by Pintong et al (2020) indicated significant mortality of Aedes aegypti (dengue fever vector) to A. conyzoides.…”
Section: Mortality Of Adult Insectsmentioning
confidence: 83%
“…and Diaphania hyalinata. Furthermore, exposure of Zonocerus variegatus to 10 mg ml -1 to 300 mg ml -1 of A. conyzoides for 4 days to 5 days induced 100% mortality of the insect pest (Ingrid et al, 2020). Similar trials by Pintong et al (2020) indicated significant mortality of Aedes aegypti (dengue fever vector) to A. conyzoides.…”
Section: Mortality Of Adult Insectsmentioning
confidence: 83%
“…Similarly, the dose (0.05g / kg), for example 50 μg/mg of body weight was administered to grasshoppers. This dose is obtained after extrapolating from previous work in the research team [15]. Then, the work carried out by [15,23] led to the adoption of the intraperitoneal route of administration in Z. variegatus since the extract is placed directly in the hemocoel.…”
Section: Justification Of Processing Parametersmentioning
confidence: 99%
“…This dose is obtained after extrapolating from previous work in the research team [15]. Then, the work carried out by [15,23] led to the adoption of the intraperitoneal route of administration in Z. variegatus since the extract is placed directly in the hemocoel. Finally, a meiotic cycle corresponds to 24 hours, that is to say one generation of spermatozoa [23].…”
Section: Justification Of Processing Parametersmentioning
confidence: 99%
See 2 more Smart Citations